China's strategy in space - Solomone, Stacey (SpringerBriefs in Space Development, 2013)
This book addresses why China is going into space and provides up- to-date information on all aspects of the Chinese Space Program in terms of launch vehicles, launch sites and infrastructure, crew vehicles for space exploration, satellite applications and scientific exploration capabilities. Beyond mere capabilities, it is important to understand how Chinese aerospace leaders think, how they make decisions, and what their ultimate goal is during their space endeavors. What are Chinese intentions in space? To what extent does culture and ethics influence Chinese strategic decision-making within the highest levels of the aerospace industrial complex? This book examines these questions and offers four potential scenarios on where the Chinese space program is headed based on this new perspective of understanding China's space goals. This book is not only required reading for policy makers and military leaders in the US government, but also for the general population, students, and professionals interested in truly understanding the reasons behind what the Chinese are doing in space.